Rituals and Magic on the Transition of Sacredness in Folk Religion in Central Vietnam - Nguyen, Dang Huu (Archīum Ateneo, 2024)
This article examines the dynamics of sacredness in Central Vietnamese folk religion. It utilizes a qualitative approach, specifically ethnographic fieldwork and in-depth interviews in the community of Danang estuary in Central Vietnam, to study rituals and magic, specifically those involved in purifying, de-sanctifying, and re-sanctifying religious artifacts. The findings of this study demonstrate that the concept of sacredness is not fixed; rather, it continuously fluctuates between states of sanctification and de-sanctification. Additionally, the dynamics of the sacred is subject to change and is attributed with different values when transferred across cultural contexts. Based on these observations, this article emphasizes the relational and dynamic nature of the sacred, and how humans attribute agency to it in order to meet their spiritual needs and achieve a sense of spiritual security both at the individual and societal levels.